Pemilihan Guru Terbaik SMP PGRI 4 Kota Jambi Metode TOPSIS dan WP - Firmansyah; Nurhadi, Nurhadi; Purnama, Benni (LPPM Universitas Dinamika Bangsa, 2025)
Decision Support System is part of an information system designed to assist the decision-making process in complex and unstructured conditions. DSS can be used in the process of selecting the best teachers, one of which is at SMP PGRI 4 Kota Jambi. The main problem is that the assessment process is still carried out manually, causing delays in processing scores and potentially leading to information leaks. To overcome this, a web-based DSS for selecting the best teachers was developed, implementing the TOPSIS and Weighted Product (WP) methods to determine the best teachers. Based on the calculation results, the TOPSIS method showed superior performance compared to WP in terms of sensitivity, which was 5.917% for TOPSIS and 5.085% for WP. However, in terms of ranking stability, the WP method is considered more consistent, where the test results show that Yuhelmi, S.Pd (A2) was predominantly selected as the best teacher at every stage of testing. Thus, the selection of the method can be adjusted to the reference used: TOPSIS excels in sensitivity of results, while WP is more stable in ranking. In addition, this system has been proven to accelerate the evaluation process and improve the efficiency of selecting the best teachers